2005
DOI: 10.1097/01.mao.0000169781.92211.76
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cement Ossiculoplasty: Incus to Stapes Versus Malleus to Stapes Cement Bridge

Abstract: Bone cement ossiculoplasty offers cost effective and significant improvement in conductive hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 11 publications
0
64
0
6
Order By: Relevance
“…Following hardening, the movement of the ossicles is checked. An exothermic reaction appears after the application of GIC [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
“…Following hardening, the movement of the ossicles is checked. An exothermic reaction appears after the application of GIC [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
“…Numerous authors [3][4][5][6][7][8][9][10] who have described the surgical steps in their GIC ossiculoplasty procedures in detail, did not mention whether the mucosa had been removed from the recipient auditory ossicle or not. Others [11][12][13][14][15] declared that the ossicle had been denuded prior to the application of the cement.…”
Section: Introductionmentioning
confidence: 99%
“…Baglam et al reported a significant hearing improvement after incudostapedial rebridging ossiculoplasty with KC (20). Bayazit et al presented a significant improvement in the hearing results of different aural pathologies and surgeries after two years of follow-up with bone cement ossiculoplasty (19). Righini-Grunder et al reported their long-term experiences by using Sereno Cem and KC GICs for different kinds of ear surgeries (9).…”
Section: +mentioning
confidence: 99%
“…Since GICs bond firmly to stapes, it may be difficult to remove it during a revision surgery. Thus, an inappropriate manipulation may cause stapes to fracture (19). The use of GICs for different ossicular reconstructions such as incus stapes re-bridging, incus augmentation, and the fixation of stapes implants have been shown by several studies as the reliable method (4,12,19,20).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation